Memahami Populasi dan Sampel: Pilar Utama dalam Penelitian Kuantitatif - Mushofa Mushofa; Dina Hermina; Nuril Huda (Syntax Corporation Indonesia, 2024)
This paper explains the importance of paying attention to research subjects in a study whose existence is a bridge between theory and practice. Because it focuses on quantitative methods, it only discusses population and samples. The method used is library research with a qualitative descriptive approach. After conducting the research, it can be concluded that population refers to the entire subject or object that is the target of research, while the sample is part of the population chosen to represent the entire population. The selection of the right population and sample is very important in research because this will affect the quality of the data, the accuracy of the results, and the conclusions drawn.